“The Lines Between Us”: Exploring the Identity of the Community Musician Through an Arts Practice Research Approach - Turner, Kathleen (Voices: A World Forum for Music Therapy, 2017)
This artist statement and video offer an extract from an auto-ethnographic performance of my learning journey as a doctoral student, titled The Lines Between Us. The video provides an example of how I used arts practice research in my doctoral thesis to bring together multiple aspects of my identity: those of singer, songwriter, community musician, and researcher. I utilised my skills as a singer and songwriter in order to better understand my practice as a community musician, to communicate my learning process to an audience, and to become a more empathetic and effective facilitator working in a field that is deeply connected to social justice. Since the video presented is a sample from a much larger work, this artist statement provides context for the reader / audience and guidance on how to engage meaningfully with the performance. In particular, this statement will consider the following: What is community music? Why arts practice research? What did this performance seek to achieve? The audience is invited to experience this performance and to further discuss its efficacy by engaging with a series of points to consider.